CD Imaging at High Spatial Resolution at Diamond B23 Beamline: Evolution and Applications - Hussain, Rohanah; Jávorfi, Tamás; Siligardi, Giuliano (Frontiers in Chemistry, 2021)
Circular Dichroism imaging in the 190–650 nm spectral region pionered at Diamond Light Source B23 beamline, has been made possible by the highly collimated microbeam generated at the beamline and has been used to study the homogeneity of the supramolecular structures of thin films of chiral materials deposited on fused quartz substrates. This facility has been expanded with the installation of a Mueller Matrix Polarimeter, MMP, coupled to the beamlight, of which a preliminary data will be discussed. In the solid state, the measurement of CD related to the supramolecular structure is hampered by the presence of circular birefringence, linear dichroism, and linear birefringence that can only be evaluated using the MMP technique. The ability to characterize the chiroptical property of thin chiral films prepared under a variety of conditions and protocols such as drop cast, spin coating, spray at different temperatures and concentrations will enable the determination of the critical parameters for reproducible, uniform and homogeneous specimen preparation, which is the sine qua non for any commercial application. This is of particular importance for optoelectronic materials, but it can also be extended to a broad variety of materials with applications from biosensors to biological tissues.